Study of Wastewater Irrigation in the Kathmandu Valley - Rutkowski, Thomas (Water Nepal, 2004)
The lack of adequate wastewater facilities and lack of rainfall during the dry season have led to the use of wastewater in agriculture in the Kathmandu Valley but wastewater irrigation has never been investigated in the monsoon climate of Nepal. This paper investigates areas of wastewater irrigation and determines wastewater irrigation practices in Kathmandu Valley.Water Nepal Vol.11(2) 2004 pp.63-71